2015
DOI: 10.1002/ejsp.2084
|View full text |Cite
|
Sign up to set email alerts
|

Substitute or stepping stone? Assessing the impact of low‐threshold online collective actions on offline participation

Abstract: Anecdotes of past social movements suggest that Internet-enabled technologies, especially social media platforms, can facilitate collective actions. Recently, however, it has been argued that the participatory Internet encourages low-cost and low-risk activism-slacktivism-which may have detrimental consequences for groups that aim to achieve a collective purpose. More precisely, low-threshold digital practices such as signing online petitions or "liking" the Facebook page of a group are thought to derail subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 71 publications
(105 reference statements)
3
71
1
1
Order By: Relevance
“…Furthermore, social media is a source of awareness raising, a tool for rapid mobilization (McGarty, Thomas, Lala, Smith, & Bliuc, ; Rainie, Smith, Schlozman, Brady, & Verba, ; Tufekci & Wilson, ), and therefore a general reinforcement to activism (Postmes & Baym, ; Postmes & Brunsting, ; Rainie et al, ) with positive rather than negative impact on offline mobilization (Christensen, ; Enjolras, Steen‐Johnsen, & Wollebæk, ). However, although it is clear that online and offline collective action engagements are strongly connected, the transfer from online participation to offline is affected by many factors, such as societal ones (Honari, ) or by the fact that individuals consider their low‐investment online actions as sufficient (Schumann & Klein, ). Indeed, some have criticized social media as a platform for easy and cheap ‘slacktivism’ replacing other forms of actions (see Christensen, ; Schumann & Klein, ).…”
Section: Social Media Use and Collective Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, social media is a source of awareness raising, a tool for rapid mobilization (McGarty, Thomas, Lala, Smith, & Bliuc, ; Rainie, Smith, Schlozman, Brady, & Verba, ; Tufekci & Wilson, ), and therefore a general reinforcement to activism (Postmes & Baym, ; Postmes & Brunsting, ; Rainie et al, ) with positive rather than negative impact on offline mobilization (Christensen, ; Enjolras, Steen‐Johnsen, & Wollebæk, ). However, although it is clear that online and offline collective action engagements are strongly connected, the transfer from online participation to offline is affected by many factors, such as societal ones (Honari, ) or by the fact that individuals consider their low‐investment online actions as sufficient (Schumann & Klein, ). Indeed, some have criticized social media as a platform for easy and cheap ‘slacktivism’ replacing other forms of actions (see Christensen, ; Schumann & Klein, ).…”
Section: Social Media Use and Collective Actionmentioning
confidence: 99%
“…Thus, using social media for instrumental purposes had the potential to maintain online engagement and support for the political cause, but it did not have the potential to transfer online activities to the actual physical occupation. In fact, the more respondents relied on the instrumentality of social media, the less motivated they were to participate in the physical protest, offering a plausible explanation why online actions do not always translate into offline protest participation (see Christensen, ; Enjolras et al, ; Schumann & Klein, ). This nicely illustrates that we need to be specific about how individuals use social media, and for what purpose, to ascertain its potential for mobilization.…”
Section: Studymentioning
confidence: 99%
“…Social movements frequently use social media for collective action, and existing research has explored how social media use can mobilize activism (e.g., Kende, van Zomeren, Ujhelyi, & Lantos, ; McGarty, Thomas, Lala, Smith, & Bliuc, ; Schumann, ; Schumann & Klein, ; Spears & Postmes, ; Thomas et al ., ). However, social media activity can fulfil diverse social change functions and scant research has examined its rhetorical functions for social movements, such as how social media may be used strategically to deploy and manage social identities within contested social movements.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the role of positive emotions in the effectiveness of social media activism is mixed. Schumann and Klein (2015) showed that online actions could derail offline actions, but not because participants were simply satisfied by feeling good about themselves. Instead, offline actions decreased because participants believed their actions were effective in enhancing the group's success, thereby negating the need for future action.…”
Section: Positive Affect and Activismmentioning
confidence: 99%